How Often Do Managers Withhold Information? - Bertomeu, Jeremy; Ma, Paul; Marinovic, Iván (The Accounting Review, 2020)
ABSTRACT We estimate a dynamic model of voluntary disclosure, using annual management forecasts of earnings, that features a manager with price motives and an uncertain, but persistent, information endowment. Our estimates imply that: (1) managers face disclosure frictions 35 percent of the time; (2) conditional on being informed, managers withhold information 17 percent of the time; and (3) conditional on being silent, managers possess information 24 percent of the time. Managers' strategic withholding motives increase investors' uncertainty about earnings by 3 percent. We find that managers' price motives reduce strategic withholding by one-third in response to investors' increased skepticism in the event of non-disclosure. JEL Classifications: D82; D83; G17.